Modifications and Trafficking of APP in the Pathogenesis of Alzheimer’s Disease - Wang, Xin; Zhou, Xuan; Li, Gongying; Zhang, Yun; Wu, Yili; Song, Weihong (Frontiers in Molecular Neuroscience, 2017)
Alzheimer’s disease (AD), the most common neurodegenerative disorder, is the leading cause of dementia. Neuritic plaque, one of the major characteristics of AD neuropathology, mainly consists of amyloid β protein (Aβ). Aβ is derived from amyloid precursor protein (APP) by sequential cleavages of β- and -secretase. Although APP upregulation can promote AD pathogenesis by facilitating Aβ production, growing evidence indicates that aberrant post-translational modifications and trafficking of APP play a pivotal role in AD pathogenesis by dysregulating APP processing and Aβ generation. In this report, we reviewed the current knowledge of APP modifications and trafficking as well as their role in APP processing. More importantly, we discussed the effect of aberrant APP modifications and trafficking on Aβ generation and the underlying mechanisms, which may provide novel strategies for drug development in AD.